140 Defining clinical and genetic biomarkers in MSA. Issue 12 (14th November 2019) - Chelban, Viorica; Woodside, John; Jabbari, Edwin; Lamb, Ruth; Bocchetta, Martina; Rohrer, Jonathan; Morris, Huw; Houlden, Henry
Abstract : Multiple System Atrophy (MSA) is a rare neurodegenerative condition. As part of the PROSPECT-M a multicentre longitudinal study building a clinical cohort of MSA patients established to improve early diagnosis and track disease progression. Patients who did not fulfil all diagnostic criteria for MSA were also recruited and followed up for phenoconversion. Functional and neuropsychology evaluations are completed at baseline and repeated after 6 and 12 months and annually for a further 3 years and include UMSARS, MoCA, ACE-3 and ECAS, comprehensive brain MRI together with a MSA biobank (plasma, serum, DNA, RNA, spinal fluid, MRI, fibroblasts). So far, 177 MSA patients were recruited of which 52 are longitudinal and 105 are crossectional. Twenty-two patients are followed-up with yearly MRI scan. All longitudinal cases have blood NFL measured yearly for tracking disease progression. We also extracted RNA from brain samples from pathologically confirmed MSA cases and pathological confirmed normal aged controls as well as from blood samples from MSA cases and control to perform expression analysis in search for novel biomarkers of disease. All MSA cases had whole genome sequencing and genotyping. The project contributes with new insights into the natural history of MSA and provides a robust longitudinal in-deapth phenotype data essential for the identification of clinical, neuroimaging and molecular signatures of the disease that can help diagnose or track disease progression.